A robust solver for wavefunction-based density functional theory calculations*This manuscript has been authored by UT-Battelle, LLC, under contract DE-AC05-00OR22725 with the US Department of Energy (DOE). The US government retains and the publisher, by accepting the article for publication, acknowledges that the US government retains a nonexclusive, paid-up, irrevocable, worldwide license to publish or reproduce the published form of this manuscript, or allow others to do so, for US government purposes. DOE will provide public access to these results of federally sponsored research in accordance with the DOE public access plan (http://energy.gov/downloads/doe-public-access-plan). (3rd February 2022) - Fattebert, J-L
Abstract: A new iterative solver is proposed to efficiently calculate the ground state electronic structure in density functional theory calculations. This algorithm is particularly useful for simulating physical systems considered difficult to converge by standard solvers, in particular metallic systems. The effectiveness of the proposed algorithm is demonstrated on various applications.